2008
DOI: 10.1017/s0022215107008547
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after surgery for benign disease of the parotid gland

Abstract: The general status of patients who have undergone surgery for a benign parotid neoplasm can be assessed with a quality of life questionnaire. Patients' post-surgical quality of life can be improved by the correct choice of surgical approach and reconstructive method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
0
10
2
Order By: Relevance
“…14,15 Others concluded, in a study on 55 patients who underwent surgery for benign neoplastic parotid disease, that the patients' postsurgical HRQOL can be improved by the choice of surgical approach and reconstructive method. 16 Nevertheless, in this study, the only significant statistical correlations were noted between general health and sex, and between postsurgical pain and sex. Another evaluation in 125 patients with parotidectomy in malignant and benign diseases showed that overall parotidectomy does not seem to severely affect quality of life.…”
Section: Introductioncontrasting
confidence: 61%
See 3 more Smart Citations
“…14,15 Others concluded, in a study on 55 patients who underwent surgery for benign neoplastic parotid disease, that the patients' postsurgical HRQOL can be improved by the choice of surgical approach and reconstructive method. 16 Nevertheless, in this study, the only significant statistical correlations were noted between general health and sex, and between postsurgical pain and sex. Another evaluation in 125 patients with parotidectomy in malignant and benign diseases showed that overall parotidectomy does not seem to severely affect quality of life.…”
Section: Introductioncontrasting
confidence: 61%
“…In studies on surgically treated benign parotid gland tumors (34 patients both) the outcome of parotidectomies had little to no impact on general HRQOL . Others concluded, in a study on 55 patients who underwent surgery for benign neoplastic parotid disease, that the patients' postsurgical HRQOL can be improved by the choice of surgical approach and reconstructive method . Nevertheless, in this study, the only significant statistical correlations were noted between general health and sex, and between postsurgical pain and sex.…”
Section: Introductioncontrasting
confidence: 61%
See 2 more Smart Citations
“…The primary difference between the two procedures is that the branching pattern and location of the facial nerve, rather than the size and extent of the tumor, determines the magnitude of dissection and the amount of parotid tissue that is removed in SP ( 4 ). Irrespective of the chosen technique, potential morbidities following parotidectomy, including pain, facial nerve paralysis, salivary fistulae, Frey’s syndrome and a loss of sensation, may affect quality of life (QoL) ( 5 , 6 ). However, successful surgery should achieve good functional results.…”
Section: Introductionmentioning
confidence: 99%